2018
DOI: 10.1111/bcpt.13025
|View full text |Cite
|
Sign up to set email alerts
|

CP‐25 Alleviates Experimental Sjögren's Syndrome Features in NOD/Ltj Mice and Modulates T Lymphocyte Subsets

Abstract: Primary Sjögren's syndrome (pSS) is a chronic inflammatory autoimmune illness of the moisture-producing glands such as salivary glands that is characterized by various immune abnormalities. The aetiology of pSS remains unclear and there is no curative agent. In this study, we investigated the putative therapeutic effects on a NOD/Ltj mouse model of Sjögren's syndrome-like disorders of an ester derivative of paeoniflorin, paeoniflorin-6'O-benzene (termed CP-25). Our study showed that CP-25 alleviated effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Our lab has reported that CP-25 could reduce pro-inflammatory cytokines production in adjuvant-induced arthritis ( Chang et al, 2016 ). Consistent with another study, CP-25 treatment showed a disease-attenuating effect on modulating T lymphocyte subsets in primary Sjögren’s syndrome mice ( Gu et al, 2018 ). Our previous study presented that paeoniflorin displayed antifibrotic effects on liver fibrosis rats induced by porcine serum ( Sun et al, 2012 ).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our lab has reported that CP-25 could reduce pro-inflammatory cytokines production in adjuvant-induced arthritis ( Chang et al, 2016 ). Consistent with another study, CP-25 treatment showed a disease-attenuating effect on modulating T lymphocyte subsets in primary Sjögren’s syndrome mice ( Gu et al, 2018 ). Our previous study presented that paeoniflorin displayed antifibrotic effects on liver fibrosis rats induced by porcine serum ( Sun et al, 2012 ).…”
Section: Introductionsupporting
confidence: 88%
“…The dysregulation of Th1/Th2 would contribute to immunologic disease, such as osteoarthritis, hepatitis, type-1 diabetes and COVID-19 pandemic. Additionally, CP-25 reduced the infiltration of Th1/Th2 cells, and reduced inflammatory cytokines production in autoantigen-induced Sjögren’s syndrome mice ( Gu et al, 2018 ). Then, we paid more attention on the relationship between CP-25 and T cell activation in ConA-induced hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…A concentration of inflammatory cytokines and anti-La/SSB and IgG antibodies in the serum from NOD/Ltj mice was repressed by CP-25. This study suggested that CP-25 is a potential agent for pSS by regulating T lymphocyte subsets (Fang et al, 2018). Taken together, CP-25 was developed which enhanced lipophilicity and strong anti-inflammatory and immune regulatory properties (Table 2).…”
Section: The Pharmacological Effects Of Cp-25mentioning
confidence: 85%
“…MDP is a novel active monomer compound, derived from a structural modi cation of paeoni orin (32). MDP has previously been discovered to have anti-in ammatory and immunomodulatory properties in a variety of autoimmune animal models (55)(56)(57). However, the effects and detailed mechanism of MDP in senescence of activated HSCs was not fully understood.…”
Section: Discussionmentioning
confidence: 99%